Pelayanan Sosial Berbasis Aset Bagi Pemerlu Pelayanan Kesejahteraan Sosial Pasca Covid-19 di Kabupaten Jember - Budhy Santoso; Atik Rahmawati; Belgis Hayyinatun Nufus; Najmudil Akbar Kadafi; Achmad Sofri Nugroho (Jurnal Intervensi Sosial dan Pembangunan, 2023)
Recovery in the health sector is still a post-covid-19 policy priority. Social services to the "Need for Social Welfare Services" focus more on charity social assistance and less on empowerment. Assistance is more for sporadic programs and tends not to consider sustainability aspects. On the other hand, the community has excellent assets that implementers can utilize in social services. As a district with the most significant number of beneficiaries in "the horseshoe" area, using community assets in social services is an alternative strategy for achieving program sustainability. This study examines Asset-Based Sustainable Social Services in Improving Empowerment of "Necessary Social Welfare Services" Post Covid-19 in the Jember Regency. The phenomenon was analyzed using a qualitative approach, with the technique of determining informants using snowball, with the key informant, the Head of the Jember District Social Service. The study results show that three community assets are utilized, including personal assets, institutions, and associations. Institutional assets show that the Social Service and BAPAS II Jember are the leading social service sectors. However, there is no synergy between the two in implementing social services. As a regional leader and authority determiner, the district head can play the role of a "Gapper", synergizing community assets through sustainable social policies.Keywords: Social services, Sustainability, Post Covid-19, Community Assets, Vulnerable People